What’re the risk factors for burned children in China? A review - Nie, Chan; Wang, Tao; Yu, Huiting; Wang, Xue; Shi, Xiuquan (Advances in Social Sciences Research Journal, 2018)
Objective: Childhood burns are a global public health problem, especially in low- and middle-income countries. This study conducted a review of children burns in order to better illustrate the risk factors of childhood burns in China. Methods: Through English and Chinese literatures, the prevalence of children burns was described, and the risk factors including age, gender, etiology of burn, season, location and the education level of guardians, lifestyle and customs were analyzed. Results: There is an estimate of 180,000 people dies from burns annually. Children under 3 years of age are the main age group of burns, and boys have a higher incidence of burns than girls. Hot fluids are the major cause of burns, and it is demonstrated that the causes of childhood burns have regional characteristics. The season that burn occurred varies from place to place. The most frequent place that burns occurred is in kitchens and bathrooms. In addition, parental education plays an important role on the prevention of child burns. Conclusion: Childhood burns can be prevented through enhancing publicity and education on burn prevention knowledge. Targeted measures should be taken to reduce the exposure of burn risk factors.